Functional Differentiation among the Arabidopsis Phosphatidylinositol 4-Phosphate 5-Kinase Genes PIP5K1, PIP5K2 and PIP5K3. (21st February 2022) - Watari, Machiko; Kato, Mariko; Blanc-Mathieu, Romain; Tsuge, Tomohiko; Ogata, Hiroyuki; Aoyama, Takashi
Abstract: Phosphatidylinositol 4-phosphate 5-kinase (PIP5K) is involved in regulating various cellular processes through the signaling function of its product, phosphatidylinositol (4, 5)-bisphosphate. Higher plants encode a large number of PIP5Ks forming distinct clades in their molecular phylogenetic tree. Although biological functions of PIP5K genes have been analyzed intensively in Arabidopsis thaliana, it remains unclear how those functions differ across clades of paralogs. We performed comparative functional analysis of the Arabidopsis genes encoding PIP5K1, PIP5K2 and PIP5K3, of which the first two and the last belong to closely related but distinct clades, to clarify their conserved and/or differentiated functions. Genetic analysis with their single and multiple mutants revealed that PIP5K1 and PIP5K3 have non-overlapping functions, with the former in total plant growth and the latter in root hair elongation, whereas PIP5K2 redundantly functions in both phenomena. This pattern of functional redundancy is explainable in terms of the overlapping pattern of their promoter activities. In transformation rescue experiments, PIP5K3 promoter-directed PIP5K1-YFP completely rescued the short-root-hair phenotype of pip5k3 . However, PIP5K3-YFP could substitute for PIP5K1-YFP only partially in rescuing the severe dwarfism of pip5k1pip5k2 when directed by the PIP5K1 promoter. Phylogenetic analysis of angiosperm PIP5Ks revealed that PIP5K3 orthologs have a faster rate of diversification in their amino-acid sequences compared with PIP5K1/2 orthologs after they arose through a eudicot-specific duplication event. These findings suggest that PIP5K3 specialized to promote root hair elongation and lost some of the protein-encoded functions retained by PIP5K1 and PIP5K2, whereas PIP5K1 differentiated from PIP5K2 only in its promoter-directed expression pattern.